Primer registro preciso de Trachemys ornata (Gray, 1831) (Testudines: Emydidae) para el estado de Jalisco, México/ First accurate record of Trachemys ornata (Gray, 1831) (Testudines: Emydidae) from the state of Jalisco, Mexico - Casas-Andreu, Gustavo; Cupul-Magaña, Fabio Germán; Chávez-Ávila, Sandra Marlen (Instituto de Ecología, A.C., 2015)
This note provides the first accurate record of the ornate slider Trachemys ornata for state of Jalisco, Mexico. Two females were recorded from Puerto Vallarta. From these records the distribution range of T. ornata is expanded to northern coast of Jalisco.